Fluid-structure interaction of a two-dimensional membrane in a flow with a pressure gradient with application to convertible car roofs - Knight, J.; Lucey, Anthony; Shaw, C. (Elsevier BV, 2010)
The flow-induced deformation of a membrane in a flow with a pressure gradient is studied. The investigation focuses on the deformation of aerodynamically loaded convertible car roofs. A computational methodology is developed with a line-elementstructural model that incorporates initial slackness of the flexible roof material. The computed flow-structure interaction yields stable solutions, the flexible roof settling into static equilibrium. The interaction converges to a static deformation within 1% difference in the displacement variable after three iterations between fluid and structural codes. Reasonably accurate predictions, to within 7%, are possible using only a single iteration between the fluid and the structural codes for the model problem studied herein. However, the deformation results are shown to be highly dependent on the physical parameters that are used in the calculation. Accurate representation of initial geometry, material properties and slackness should be found before the predictive benefits of the fluid-structure computations are sought. The iterative methodology overcomplicates the computation of deformation for the relatively small displacements encountered for the model problem studied herein. Such an approach would be better suited to applications with large amplitude displacements such as those encountered in sail design or deployment of a parachute.